The Involvement of the Intestinal Microflora in theExpansion of CD4+ T Cells with a‐Naive Phenotype inthe Periphery - Ruud Dobber; Anita Hertogh‐Huijbregts; Jan Rozing; Kim Bottomly; Lex Nagelkerken (1992)
It is well known that immune reactivity declines with age. Recently, we demonstrated that the age‐related decrease in IL‐2 production by CD4 + T cells was accompanied by an increased production of IL‐4 and interferon‐ γ ,(IFN‐ γ ). This age‐related shift in the profile of lymphokine production was related to phenotypic changes within the CD4 + T‐cell subset, that is, a decrease in the percentage of CD45RB ++ CD4 + T cells and an increase in the percentage of Pgp‐1 + CD4 + T cells. To study whether these age‐related changes were due to previous antigenic exposure, we performed a phenotypic and functional analysis on splenic CD4 + T cells isolated from individual, germ‐free (GF), specific pathogen‐free (SPF), and clean conventional (CC) mice. Interestingly, the total number of splenic CD4 + T cells in GF mice was twofold lower as compared to age‐matched SPF or CC mice, regardless whether mice were analyzed at young (10 weeks) or at advanced age (13‐14 months). Unexpectedly, the phenotypic composition of the CD4 + T‐cell subset was comparable in the GF, SPF, and CC mice as determined by the expression of CD45RB and Pgp‐1, indicating that CD4 + T cells with a naive phenotype (CD45RB ++ Pgp‐1 – ) were not enriched in GF mice. Moreover, at an age of 13–14 months, CD4 + T cells from GF mice frequently produced more IL‐4 and IFN‐ γ , than their CC counterparts. These lymphokine data showed, therefore, that a relatively high proportion of CD4 T cells with a memory phenotype can also be defined in GF mice on the basis of their function. The contamination of GF mice with a colonization resistant factor (CRF flora) resulted in twofold higher numbers of splenic CD4 + T cells. Surprisingly, not only CD4 + T cells with a memory phenotype (CD45RB –/+ Pgp‐1 ++ ) had expanded, but also CD4 + T cells with a naive (CD45RB ++ Pgp‐1 – ) phenotype. Our results, therefore, strongly suggest that the expansion of naive CD4 + T cells in the periphery is mediated by the intestinal microflora.